MAKNA SIMBOLIS SRIMPI LIMA PADA UPACARA RUWATAN DI DESA NGADIRESO PONCOKUSUMO MALANG - Ninik Harini (Fakultas Sastra Universitas Negeri Malang, 2012)
In Ngadireso, Poncokusumo, Malang, Srimpi Lima dance is perfomed by five dancers wearing similar costume but different color of Sampur. The floor pattern is also rectangular which allows clockwise movement for the dancers. Moreover, this dance also has symbolical meaning due to its function as Ruwatan ceremony for ontang-anting or for the only child who belongs to sukerta child. The aim of this study is not only to describe the perfomance and the function but also the symbolical meaning of Srimpi Lima dance in Ruwatan ceremony. To obtain clear description of this study, the researcher applied qualitative - descriptive research through interview, observation and documenting; and document collection. The procedure of the research was conducted through several stages, they are:planning, conducting the research, data analysis, and data presentation. The result of the study shows that the symbolical meaning of Srimpi Lima dance is intended to purify the Sukerta child.